2019
DOI: 10.1080/21688370.2019.1593775
|View full text |Cite
|
Sign up to set email alerts
|

Chloride intracellular channel protein 2 in cancer and non-cancer human tissues: relationship with tight junctions

Abstract: 2019) Chloride intracellular channel protein 2 in cancer and noncancer human tissues: relationship with tight junctions, Tissue Barriers, 7:1, 1593775, ABSTRACT Chloride intracellular channel protein 2 (CLIC2) belongs to the CLIC family of conserved metazoan proteins. Although CLICs have been identified as chloride channels, they are currently considered multifunctional proteins. CLIC2 is the least studied family member. We investigated CLIC2 expression and localization in human hepatocellular carcinoma, metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
21
1
Order By: Relevance
“…CLIC2 , the other locus involved in the duplication and also speculated to contribute to the syndrome's manifestations, has been shown to be under‐expressed in hepatocellular carcinoma and colorectal adenocarcinoma, with its expression levels paralleling those of tight junctions. This suggested a possible role for CLIC2 in maintaining cell–cell adhesion and preventing hematogenous dissemination of tumor cells (Ueno et al, 2019). However, it is unclear whether an increase in gene dosage of CLIC2 as occurs in the syndrome would have similar effects in promoting oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…CLIC2 , the other locus involved in the duplication and also speculated to contribute to the syndrome's manifestations, has been shown to be under‐expressed in hepatocellular carcinoma and colorectal adenocarcinoma, with its expression levels paralleling those of tight junctions. This suggested a possible role for CLIC2 in maintaining cell–cell adhesion and preventing hematogenous dissemination of tumor cells (Ueno et al, 2019). However, it is unclear whether an increase in gene dosage of CLIC2 as occurs in the syndrome would have similar effects in promoting oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CLIC2 was found in endothelial cells in blood vessels, but not lymphatic vessels, in non-cancerous tissues, and its expression is significantly lower when compared to endothelial cells of blood vessels in cancerous tissues. Ablation of CLIC2 in human umbilical vein endothelial cells (HUVECs) compromised the integrity of the vessels and allowed human cancer cells to transmigrate through a HUVEC monolayer (Ueno et al, 2019). In addition to CLIC2, CLIC1, and CLIC4 are also known to be present in endothelial cells (Suh et al, 2005b;Money et al, 2007;Tung and Kitajewski, 2010;Wegner et al, 2010), and CLIC5 is present in placental as well as glomerular endothelial cells (Money et al, 2007;Wegner et al, 2010).…”
Section: Clics In Cardiovascular and Pulmonary Functionmentioning
confidence: 99%
“…CLIC2 is not reported as a cancer gene in the network of cancer genes' (NCG 6.0) collection of sources of known cancer genes and 273 cancer mutation screenings (Repana et al, 2019). However, recently it was shown that CLIC2 is highly expressed in non-cancerous cells surrounding cancer masses (Ueno et al, 2019). Expression of CLIC2 and other tight junction proteins such as claudins 1 and 5, occludin and ZO-1 were significantly higher in non-cancer cells as compared to human hepatocellular carcinoma.…”
Section: Clic2mentioning
confidence: 99%
See 1 more Smart Citation
“…From the biological perspective, the chloride intracellular channel (CLIC) family represented by CLIC1-6 constitutes a subgroup of the glutathione-Stransferase (GST) superfamily [31][32][33]. Ion channels play important roles in the development of cancer and their expression is known to be altered in cancer cells [12,34].…”
Section: Discussionmentioning
confidence: 99%